2020
DOI: 10.1128/iai.00289-20
|View full text |Cite
|
Sign up to set email alerts
|

Conserved ESX-1 Substrates EspE and EspF Are Virulence Factors That Regulate Gene Expression

Abstract: Mycobacterium tuberculosis, the cause of human tuberculosis, and Mycobacterium marinum, a non-tubercular pathogen with a broad host range, require the ESX-1 secretion system for virulence. The ESX-1 system secretes proteins which cause phagosomal lysis within the macrophage via an unknown mechanism. As reported in R.E. Bosserman et al (Proc Natl Acad Sci U S A doi:10.1073/pnas.1710167114), we recently discovered that the ESX-1 system regulates gene expression in M. marinum This finding has been confirmed in M.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(98 citation statements)
references
References 82 publications
2
73
0
Order By: Relevance
“…EsxA mediates mycobacterial escape from the phagosome and translocation to the cytosol (here termed cytosolic translocation) through its acidic-pH-dependent membrane-permeabilizing activity (MPA) that disrupts lipid membranes at low pH ( Figure 1 ) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Interestingly, other mycobacterial factors are also involved in mycobacterial cytosolic translocation, and the co-dependent expression and secretion of EsxA with other factors increases the complexity of dissecting the precise roles of EsxA in mycobacterial pathogenesis [ 43 , 53 , 54 , 55 ]. Moreover, EsxA is a strong immunoregulator and interacts with multiple cellular proteins and signaling pathways [ 35 , 36 , 40 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…EsxA mediates mycobacterial escape from the phagosome and translocation to the cytosol (here termed cytosolic translocation) through its acidic-pH-dependent membrane-permeabilizing activity (MPA) that disrupts lipid membranes at low pH ( Figure 1 ) [ 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 ]. Interestingly, other mycobacterial factors are also involved in mycobacterial cytosolic translocation, and the co-dependent expression and secretion of EsxA with other factors increases the complexity of dissecting the precise roles of EsxA in mycobacterial pathogenesis [ 43 , 53 , 54 , 55 ]. Moreover, EsxA is a strong immunoregulator and interacts with multiple cellular proteins and signaling pathways [ 35 , 36 , 40 , 56 , 57 , 58 , 59 , 60 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, deletion of other ESX-1 substrates would impact mycobacteria phagosome escape ability [ 17 , 38 ]. A recent study has reported that deletion of espE/F significantly inhibits Mm’s hemolysis, while the expression and secretion of EsxA/B were not affected [ 77 ], indicating that EsxA and EsxB are not sufficient for mycobacteria lysis-related phenotype. We also notice that deletion of espE or espF upregulates the expression and secretion of EsxA and EsxB, which provides an evidence that genetic deletion may introduce artifacts by altering expression of other genes.…”
Section: Discussionmentioning
confidence: 99%
“…EspE and EspF negatively regulate the esx -1 locus through WhiB6 transcription factor (Chirakos et al ., 2020 [68], Sanchez et al ., 2020 [69]) inside cytoplasm and after secretion promote virulence and lytic activity (Chirakos et al ., 2020 [68]).…”
Section: Introductionmentioning
confidence: 99%
“…EspM negatively regulate the esx -1 locus through WhiB6 transcription factor (Chirakos et al ., 2020 [68], Sanchez et al ., 2020 [69]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation